Prevent Child Marriage by Improving Education in West Nusa Tenggara Through Sister Province Relations with Kujawsko-Pomorskie, Poland - Musawar, Musawar; Riadhussyah, M.; Bukhari, Ahmad Saifuddin; Subarkah, Alwafi Ridho (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2022)
This study aims to determine the local government's efforts to prevent child marriage by establishing foreign relations with other countries in education, in this case, the Province of West Nusa Tenggara (NTB) and Kujawsko-Pomorskie, Poland. This foreign relationship is carried out by NTB as an effort to increase human resources through education with a country with very good quality education, namely Poland. This research method is descriptive-qualitative with the concept of sister province and the concept of Para diplomacy, which provides space for local governments to conduct foreign relations with other countries. The technique of collecting data by conducting a literature study is by examining various secondary sources in the form of books, articles, official news, and online news that are relevant to this research. The data analysis technique is through the stages of data collection, data reduction, data presentation, then drawing conclusions. The results of this study indicate that the existence of foreign relations in the context of sister provinces carried out by the Provinces of NTB, Indonesia, and Kujawsko-Pomorskie, Poland was initiated by the leaders of each province which then paved the way for educational cooperation between institutions in the two provinces. So that through this educational collaboration, the NTB Provincial Government can encourage the improvement of the quality of education which is expected to strengthen human development and prevent child marriage.